Integração do sistema acadêmico da Universidade Federal de Santa Maria - UFSM a uma smart classroom - Raffaelli, Rafael (2019)
In Latin America most of the class time is consumed by administrative tasks performed by teachers, including the conference of students attendance. Classrooms are energetically transformed by technology, through which it is possible to apply knowledge about space and its members and improve their experience. From this perspective, characterized by smart cities and campuses, came the smart classroom derivation. Building a smart classroom can help reduce the time spent doing such a task, as well as improve the environment through sensor monitoring. Building a smart classroom in isolation limits its benefits, but integrating it with existing educational software enriches them and can automate processes. Thus, the present work proposes the integration of a smart classroom to the academic system of the Federal University of Santa Maria - UFSM, in order to reduce the time spent by the teacher for the conference of the students attendance. In order to achieve the objectives, searches were made with the literature of technologies involved in the integration of legacy systems to this new computational architecture. Secondly, the operating processes, scope delimitation, selection of the hardware and software necessary for the creation of the smart classroom and the development of the integration tool called SIoT were defined. . Finally, the implementation of the prototype in the classroom, which was validated with four undergraduate classes of the Information Systems and Computer Science courses. It was observed a reduction of up to 92,19% of the time spent for the conference of students attendance, compared to the methods currently used by the institution. In addition, the work was successful in creating and integrating with the academic system of the institution, and may eventually be an integral part of it permanently. The dissertation is inserted in the research line Educational Software Development, linked to the Graduate Program in Educational Networked Technologies, and resulted the text presented here, together with the integration module between smart classroom and the academic system of the institution.